2013
DOI: 10.9779/puje612
|View full text |Cite
|
Sign up to set email alerts
|

A Scientist Created in the Picture that Pre-service Teachers have in their Minds

Abstract: ÖzetBu betimsel çalışmada, öğretmen adaylarının zihinlerinde canlanan resimden hareketle bir bilim insanını nasıl gördükleri açığa çıkarılmaya çalışılmıştır. Çalışma, sınıf öğretmenliği programının son sınıfına kayıtlı toplam 104 gönüllü öğretmen adayından, yarı yapılandırılmış anket aracılığıyla toplanan verilere dayalı olarak gerçekleştirilmiştir. Bulgular, öğretmen adaylarının zihinlerindeki öncelikli bilim insanı isminin Einstein olduğunu göstermektedir. Ayrıca üç başlık altında oluşan, toplam yedi temadan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
6
0
5
Order By: Relevance
“…Based on the image of scientists and the level of science/pseudoscience distinction levels of prospective teachers of gifted education and elementary education, it was revealed that the prospective teachers reflected stereotypical perceptions towards scientists in their drawings in general. In the same way as many studies in the literature (Bozdoğan, Şengül and Bozdoğan, 2013;Camci-Erdogan, 2018;Çermik, 2013;Moseley and Norris, 1999;Özkan et al 2017;Reap, Cavallo and McWhirter, 1994;Şenel and Aslan, 2014;Ünver, 2010;Ürey et al 2017) the teacher candidates of both gifted education and elementary education portrayed scientists mainly as a middleaged, messy-looking person wearing a laboratory coat and glasses and working alone on chemicals in the laboratory. As a result of comparison between the two groups based on the stereotypical images in the drawings of scientists, it was revealed that the teacher candidates of elementary education had more stereotypical image and perception for scientists.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Based on the image of scientists and the level of science/pseudoscience distinction levels of prospective teachers of gifted education and elementary education, it was revealed that the prospective teachers reflected stereotypical perceptions towards scientists in their drawings in general. In the same way as many studies in the literature (Bozdoğan, Şengül and Bozdoğan, 2013;Camci-Erdogan, 2018;Çermik, 2013;Moseley and Norris, 1999;Özkan et al 2017;Reap, Cavallo and McWhirter, 1994;Şenel and Aslan, 2014;Ünver, 2010;Ürey et al 2017) the teacher candidates of both gifted education and elementary education portrayed scientists mainly as a middleaged, messy-looking person wearing a laboratory coat and glasses and working alone on chemicals in the laboratory. As a result of comparison between the two groups based on the stereotypical images in the drawings of scientists, it was revealed that the teacher candidates of elementary education had more stereotypical image and perception for scientists.…”
Section: Discussionmentioning
confidence: 69%
“…Studies in the literature are mostly concerned with the students but also some studies conducted with the teacher candidates. These studies are mostly conducted with elementary teacher candidates (Çermik, 2013;Reap, Cavallo and McWhirter, 1994;Ünver, 2010), mixed groups (science, social studies, elementary, music etc.) (Bozdoğan, Şengül and Bozdoğan, 2013;Moseley and Norris, 1999;Özkan et al,2017;Ürey et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Konu ile ilgili daha önce yapılan çalışmalarda da özellikle görsel medya ve ders kitaplarının kalıp bilim insanı imajlarının oluşmasında ciddi bir etken olduğu ortaya koyulmuştur (Camcı-Erdoğan, 2013a, 2013bSchibeci, 1986;Song ve Kim, 1999;Yontar-Toğrol, 2000 (Çermik, 2013;Reap, Cavallo ve McWhirter, 1994;Ünver, 2010;Yetim, 1996) da görülen bu sonucun öğretmen adaylarının sahip olduğu imajlar üzerinde; TV, sinema, gazete vb. medya araçlarında özellikle bilim insanlarının laboratuvar ortamında "deney tüpleri, kimyasallar vb.…”
Section: Tartışma Ve Sonuçunclassified
“…laboratuvar araç ve gereçleri" ile toplumdan tecrit olmuş, uzak bir mekânda yalnız çalışırken resmedilmesinden kaynaklandığı söylenebilir. Bu durum üzerinde daha önceki çalışmalarda da (Camcı-Erdoğan, 2013a, 2013bSchibeci, 1986;Song ve Kim, 1999;Türkmen, 2008;Yontar-Toğrol, 2000) (Buldu, 2006;Camcı-Erdoğan, 2013a, 2013bChambers, 1983;Çermik, 2013;Flick, Fort ve Varney, 1989;Fung, 2002;Gonsoulin, 2001;Kaya, Doğan ve Öcal, 2008;Kemaneci, 2012;Mead ve Metraux, 1957;Narayan et. al., 2007;Schibeci, 2006;Song ve Kim, 1999;Symington ve Spurling, 1990;Türkmen, 2008;Ünver, 2010;Yontar-Toğrol, 2000) Günümüze kadar yapılmış birçok çalışma öğretmenlerin bilime/ bilim insanına yönelik sahip oldukları tutumların, ilgi ve imajların öğrencilerin de sahip olduğu tutum, ilgi ve imajları etkilendiğini ortaya koymuştur (Altınok, 2004;Morell ve Lederman, 1998;Palmer, 2001…”
Section: Tartışma Ve Sonuçunclassified
“…Nowadays it is expected that the individuals who are raised due to the developments in science and technology can keep up with these changes, solve the problems they encounter and can produce innovation from existing information [10]. In other words, it is planned to train individuals who can turn mathematical thinking and reasoning skills into life-style [11].…”
Section: Introductionmentioning
confidence: 99%